Cationic Vesicles Based on Amphiphilic Pillar[5]arene Capped with Ferrocenium: A Redox‐Responsive System for Drug/siRNA Co‐Delivery1. Issue 48 (29th September 2014) - Chang, Yincheng; Yang, Kui; Wei, Peng; Huang, Sisi; Pei, Yuxin; Zhao, Wei; Pei, Zhichao
Abstract A novel ferrocenium capped amphiphilic pillar[5]arene (FCAP) was synthesized and self‐assembled to cationic vesicles in aqueous solution. The cationic vesicles, displaying low cytotoxicity and significant redox‐responsive behavior due to the redox equilibrium between ferrocenium cations and ferrocenyl groups, allow building an ideal glutathione (GSH)‐responsive drug/siRNA co‐delivery system for rapid drug release and gene transfection in cancer cells in which higher GSH concentration exists. This is the first report of redox‐responsive vesicles assembled from pillararenes for drug/siRNA co‐delivery; besides enhancing the bioavailability of drugs for cancer cells and reducing the adverse side effects for normal cells, these systems can also overcome the drug resistance of cancer cells. This work presents a good example of rational design for an effective stimuli‐responsive drug/siRNA co‐delivery system.